Money Demand and Inflation in Dollarized Economies : The Case of Russia - Ohnsorge, Franziska (IMF Working Papers; Working Paper, 2005)
Money demand in dollarized economies often appears to be highly unstable, making it difficult to forecast and control inflation. In this paper, we show that a stable money demand function for Russia can be found for "effective broad money," which includes an estimate of foreign cash holdings. Moreover, we find that an excess supply of effective broad money is inflationary, while other excess money measures are not, and that effective broad money growth has the strongest and most persistent effect on short-run inflation.